Classical and Contemporary Fiqh Approaches to Re-Estimating the Zakat Potential in Indonesia - Maya Asfarina; Ascarya Ascarya; Irfan Syauqi Beik (Bank Indonesia, 2019)
This study aims to re-estimate the potential of zakat in Indonesia based on the classical and contemporary fiqh approaches, as well as including optimistic and realistic scenarios with different assumptions. Under the classical fiqh approach, the potential amount of zakat was calculated based on the zakatable assets that have been agreed upon by all scholars, including only zakat on savings. Meanwhile, using the contemporary fiqh approach, the zakat potential was calculated based on a new classification of zakatable assets agreed by contemporary scholars after considering the issue of economic development, including professional (household) zakat, corporate zakat and zakat on savings. The results show that, based on the classical fiqh approach, the potential zakat amount is IDR 69.57 trillion, or equivalent to 0.56% of GDP under the optimistic scenario, and it is IDR 13.26 trillion, or equivalent to 0.11% of GDP, under the realistic scenario. Meanwhile, based on the contemporary fiqh approach, the potential zakat amount is IDR 216.54 trillion, or equivalent to 1.75% of GDP, under the optimistic scenario, and it is IDR 74.87 trillion, or equivalent to 0.60% of GDP, under the realistic scenario. The estimated zakat potentials are still significantly higher than actual zakat collection recorded. However, the results of classical approach under the realistic scenario (0.11% of GDP) is the closest to the real 2018 zakat collection of 0.05% of GDP, which could be the indication that most Indonesian Muslims follow classical fiqh approach in calculating their zakat maal obligation.